Re-evaluating Floor Space Allowance and Removal Strategy Effects on the Growth of Heavyweight Finishing Pigs - J. R. Flohr; M. D. Tokach; John F. Patience; G. Gourley; J. M. DeRouchey; S. S. Dritz; J. C. Woodworth; R. D. Goodband (Kansas Agricultural Experiment Station Research Reports, 2015)
This study was performed to evaluate the impact of initial floor space allowance and various topping strategies (removal of the heaviest pigs in a pen prior to marketing the finishing group) on the growth performance of heavyweight finishing pigs. A total of 1,092 pigs (initially 80.1 lb) were allotted to one of 4 experimental treatments with 14 pens per treatment. The first treatment stocked pigs at 9.7 ft2(15 pigs/pen) throughout the study. The other three treatments initially stocked pigs at 6.9 ft2. The second treatment (2:2:2) topped the two heaviest pigs on d 64 (203 lb), d 76 (227 lb), and d 95 (264 lb), which coincided with the time floor space allowance became limiting, as predicted by Gonyou et al. (2006). The third treatment (2:4) topped the 2 heaviest pigs and the 4 heaviest pigs at an average BW of 240 (d 76) and 280 lb (d 105), respectively. The fourth treatment (6) topped the 6 heaviest pigs at an average BW of 280 lb (d 105). All pigs remaining in pens after topping events were marketed on d 117 of the study. Overall (d 0 to 117), pigs in pens stocked at 9.7 ft2had increased (P<0.05) ADG compared to pigs in pens on either the 2:4 or 6 topping strategies, but ADG was not different from pigs in pens on the 2:2:2 topping strategy. This suggests that prediction equations developed by Gonyou et al. (2006) for ADG are useful for predicting the effects of floor space on heavyweight pig ADG. Pigs in pens stocked at 9.7 ft2had increased (P<0.05) ADFI compared to pigs in pens initially stocked at 6.9 ft2regardless of topping strategy. Total weight gain per pen was greater (P<0.05) for pens initially stocked at 6.9 ft2compared to pens stocked at 9.7 ft2; however, total weight gain per pig was greater for pigs in pens stocked at 9.7 ft2compared to pigs in pens initially stocked at 6.9 ft2. Pigs in pens on the 2:2:2 topping strategy had less weight gain (P<0.05) than pigs in pens on the 6 topping strategy. Feed usage per pen was decreased for pens stocked at 9.7 ft2compared to those initially stocked at 6.9 ft2; however, per pig feed usage was increased (P<0.05) for pigs in pens stocked at 9.7 ft2compared to pigs in pens initially stocked at 6.9 ft2. Pens on the 2:2:2 topping strategy had less (P<0.05) feed usage, either on a pen or pig basis, than those on the 2:4 or the 6 topping strategy. Interestingly, there was a tendency (P<0.10) for pigs in pens on the 2:4 topping strategy to have less feed usage than pigs in pens on the 6 topping strategy. Income over feed and facility cost (IOFFC) was decreased (P<0.05), either on a pen or pig basis, for pens stocked at 9.7 ft2. Pigs in pens on the 2:2:2 topping strategy had numerically less IOFFC when revenue was high and feed cost was low compared to pigs in pens on the 2:4 or 6 topping strategy. In conclusion, increasing the floor space allowance or the time points at which pigs are removed from the pen improved the performance of pigs remaining in the pen; however, IOFFC may be reduced due to fewer pigs marketed from each pen (in the case of lower stocking density) or from reducing total weight produced (in pens where pigs are topped earlier at lighter weights).
Keywords: finishing pig; floor space; growth; topping